ANALISIS SIKAP GURU TK TERHADAP PEMBELAJARAN MATEMATIKA DI KECAMATAN BINA WIDYA KOTA PEKANBARU - Miftahul Jannah; Yeni Solfiah; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The background of this research is because according to researchers learning mathematics is a difficult lesson for children, let alone early childhood even we as adults experience difficulties when learning mathematics. the purpose of this study was to determine the attitude of kindergarten teachers towards learning Mathematics in Bina Widya District, Pekanbaru City. This research is quantitative descriptive. The research population is 312 teachers in Bina Widya District. The sample used was 76 teachers. To determine the sample of this research using random sampling technique. Methods of data collection by using a questionnaire. The data analysis technique used is a quantitative descriptive analysis technique using the percentage formula. Based on the results of the study it can be concluded that the attitude of kindergarten teachers towards learning mathematics in this behavioral aspect is in the sufficient category. Because teachers are less enthusiastic about using APE in learning mathematics, the lack of use of learning media for learning mathematics, and making games in learning mathematics. Keywords: Teacher Attitude, Mathematics Learning